Challenges in ACS - DeLemos, James; Bhatt, Deepak; Cushman, Mary; Berger, Peter B. (MD Conference Express, 2005)
“We need to be cautious about ‘cookbook’ approaches that do not account for individual patient variations,” said James DeLemos, MD, Associate Professor, University of Texas Southwestern Medical Center, Dallas, acknowledging that patient variations can be difficult to appreciate on clinical grounds alone (e.g., history, PE, ECG); which makes biomarkers all the more important.